Association of SNPs in ESR1 and ESR2 Genes with Egg Production in Anand Synthetic White Leghorn and Anand Bantamised White Leghorn Chicken - Parmar, Glory S; Patel, Devanshi V; Kachchhi, Ankit V; Patel, Ashish C; Patel, Atul B; Koringa, Prakash G (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The objective of the present study was to find Single Nucleotide Polymorphisms (SNPs) in ESR1 and ESR2 genes and examine their association with egg production in chickens up to 64 weeks of age (EN64). Blood samples were taken from 48 Anand Synthetic White Leghorn (ASWLH) and 48 Anand Bantamised White Leghorn (ABWLH) chickens. Amplicon sequencing was carried out using the IlluminaMiseq platform, and a custom panel was developed to cover the exon regions of these genes. Total 91 SNPs, 59 previously reported and 32 novel SNPs were identified from 96 samples. In conclusion, the genetic variants g.52944897 T>C and rs3181386 inside the ESR2 gene exhibit potential as selection markers linked to EN64 in chickens.